الحجاج البلاغي في سورة مريم - الخزاعي فاطمة عبد زيد شوين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In The Name of Allah Most Gracious Most Merciful. Praise be to God, the first without another after him, whom the eyes of the beholders fail to see, and the delusions of the descriptors fail to describe him, and may God’s blessings be upon Muhammad and his pure household and his chosen companions. As for after... In this research, we seek to trace the arguments that appear in Surat Maryam, and to come across the most prominent persuasion therein; The arguments of the infidels and the enemies of Mary, and the Qur’anic text is full of irrefutable rhetorical arguments that cannot be answered by the flimsy arguments of the infidels. According to the foregoing, the research section deals with the argumentative discourse in Surat Maryam, and the second topic is the argumentative rhetoric.